Дослідження впливу тиску рідкого харчового продукту на закон переміщення клапана прецензійного дозатора - Якимчук, Микола Володимирович; Горчакова, Ольга Миколаївна; Токарчук, Сергій Володимирович; Валіулін, Геннадій Раіфович (My University, 2018)
У статті розглядаються впливи змін тиску рідкого харчового продукту в каналі дозування на закони переміщення клапана прецензійного дозатора. В результаті досліджень отримано аналітичну модель зміни тиску в каналах дозувального пристрою для випадку закриття клапану дозатора рідкого харчового продукту. Отримані результати можливо в подальшому використовувати при проектуванні системи керування прецензійних дозаторів нового покоління, які реалізують задані закони руху. The change in pressure of a liquid food product in the dosing channel on the laws of the movement of the valve of the precision dispenser discusses in the article. It has been established that the dosage of a liquid food product is a complex process which is connected with non-stationary modes of opening and closing of the actuating device. The quality of such a process essentially depends on the kinematic and dynamic parameters of the movement of a liquid food product. The most important part of the dosing system is the locking element at the dosing liquid food product which is in direct contact with the dosed liquid. The conical and cylindrical locking elements are the most common. Traditionally, linear, parabolic and step laws of motion are used to implement the movement of the locking element. The listed laws of motion consist of three main stages: from opening, idle and closing. The most accurate for dosing is the parabolic law of motion of the dispenser valve which ensures the smoothness of that valve in the final stage. According to the results of analytical researches it was found that there is a sharp increasing in pressure in the dosing channels at the time of closing. This phenomenon is accompanied by a hydraulic shock on the valve which is characterized by a significant excess of the nominal pressure in the hydraulic system. The authors proposed to implement the fourth stage of the movement of the check valve for high-quality work of a control system of the dispenser. This will affect the transient, which is crucial for the accuracy of dosing. The results can be further used in the design of the new generation precision dispensers control systems, which implement the specified laws of motion of the valve.
Keywords: дозування; рідкий харчовий продукт; клапан; тиск; прецензійний дозатор; dosing; liquid food; valve; pressure; precision dispenser; кафедра мехатроніки та пакувальної техніки